Frequency and Clinical Profile of Cardiac Arrhythmias and its Immediate Outcome in Children at Tertiary Care Hospital - Ali Raza, Abdul Sattar Shaikh, Hussain Bux Korejo, Rumana Sangi, Aliya Kemal Ahasan, Shakeel Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency and clinical profile of arrhythmia and its immediate outcome in children presenting to a tertiary care center. Study Design: A cross-sectional study. Duration and place of study: July 2021 to June 2022, the National Institute of Cardiovascular Diseases, Karachi. Methodology: A total of 100 children of both gender , ranging in age from 1 day to 18 years, who presented with the symptoms of syncope, decreased or increased heart rate, chest discomfort, breathlessness were included in this study. Children who presented with cardiac arrhythmias had varying proportions of several criteria of relevance, such as clinical characteristics, age and gender distribution. In patients with unexplained arrhythmias or syncope, a thorough history, general physical exam, and cardiac examinations—including 12-lead electrocardiograms, 2-D echocardiograms, and Holter studies—were conducted. Results: A total of 100 children were included in this study among them 70 children presented with tachyarrhythmia and 30 children presented with bradycardia. The average age was 8.13± 4.45 years. Among the tachyarrythmias group the most frequent initial symptoms recorded in 45 (64.28%) and 15 (21.42%) youngsters, respectively, were palpitation and chest pain. A total of 19 (27.14%) children were discovered to have acyanotic CHDs. SVT was found to be the most common type of arrhythmia in 25 (30.1%) children, followed by ventricular tachycardia and atrial fibrillation in 15 (21.42%) and 10 (14.28%) of the same age groups. A total of 3 (4.28%) of the hospitalized children died. Among the bradycardia group 80% of children were found with complete heart block, 53.3% syncope, 26.7% were asymptomatic, and 20% were with multiple findings of irritability, poor feeding, breathlessness, and syncope. 20% of them developed LV dysfunction. Conclusion: The most frequent presenting symptoms were palpitations and chest discomfort. The other most common types of arrhythmia were supraventricular tachycardia, atrial fibrillation, ventricular tachycardia and bradycardia. Children's hospital stays were generally short and the therapy for arrhythmias had favorable overall results, however, 4.28% of children in the tachyarrhythmia’s group died of heart failure, while there was no expiry in the bradycardia group. Keywords: Arrhythmias, palpitations, supraventricular and ventricular tachycardia, bradycardia and heart Block